Study on magnetic behaviors in a diluted ferrimagnetic Ising graphene nanoribbon - Sun, Lei; Wang, Wei; Li, Qi; Wang, Feng; Wu, Hao-Jia (Superlattices and microstructures, 2020)
By applying the Monte Carlo simulation, the magnetic behaviors of the zigzag graphene nanoribbon have been studied based on the diluted ferrimagnetic mixed spin-3/2 and spin-5/2 Ising system. We have discussed the temperature dependence of the magnetization, magnetic susceptibility and the internal energy curves caused by different anisotropies, external magnetic field and magnetic atom concentration in detail. The phase diagrams for various physical parameters were given. Moreover, multi-loop hysteresis behaviors under the effects of different Hamiltonian parameters have been investigated. •The diluted ferrimagnetic mixed spin-3/2 and spin-5/2 Ising zigzag graphene nanoribbon has been investigated.•Magnetization, susceptibility and internal energy have been presented.•The effects of different anisotropies, external magnetic field and magnetic atom concentration have been discussed.•The phase diagrams of the blocking temperature under the influence of different parameters have been obtained.•The multi-loops hysteresis behaviors have been observed for certain Hamiltonian parameters.